Development of electronic modules using flip pdf professional physics mathematics I folding integral materials course - Chen, Diki; Ramadhanti, Auliya (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2024)
The purpose of this study was to determine the results of the development of an electronic module on multiple integral materials and students' perceptions of the product being developed. The type of research conducted is R&D research with the chosen development model being the 4-D development model. The research sample used was two expert lecturers as product assessors and 25 students as samples whose perceptions were measured. The sampling technique used was purposive sampling with the instruments used were student needs questionnaires, material validation, media validation, and student perceptions. Data analysis for the questionnaire is descriptive statistics, while for instrument validation data using reliability and validity tests. The results of the data obtained indicate that the product is feasible to use and can be accessed using a mobile phone via the link provided by the author, while the perception of the electronic module obtained shows a very good perception. Thus, this module is considered feasible and ready to be used to assist students in understanding the multiple integral materials.